Slope Stability Analysis of Pit X on Nickel Mining Based on Comparison between Design and Actual Mining Condition - Purwanto Purwanto; Tegar Abadi (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2024)
The nickel laterite mining on the slopes of pit X uses the open-cast mining method with material strength conditions similar to soil. Slope stability considerations under temporary conditions such as earthquakes and increased groundwater levels due to rain need to be reviewed as a precaution against landslides. Limonite and saprolite materials have varying cohesion and phi values that affect the safety factor value. The probability function describes the distribution of a random variable to estimate the probability value of a parameter. The limit equilibrium method can indicate the probability of failure. The pit X slope is designed with a bench height of 10 meters, a bench width of 7 meters, and a single slope inclination of 45˚, but after mining, the slope geometry and material distribution conditions change. Stability analysis of the pit X by comparing design and actual conditions after mining is conducted to determine the safety factor comparison under various soil conditions in both design and actual states. The analysis is performed using the Unified Soil Classification System (USCS) classification method and the Morgenstern-Price (MP) limit equilibrium method. All sections meet the slope stability criteria based on the minimum safety factor standards of 1.30 for static conditions, 1.10 for dynamic conditions, 1.0 for saturated soil conditions, and a probability of failure of <5%. However, based on the results of physical property tests, slope stability needs to be reviewed periodically due to the potential for landslides. Sections A-A' and D-D' have steeper overall slopes in the actual condition, resulting in lower safety factors than in the design condition. Sections B-B' and C-C' have gentler overall slopes in the actual condition, resulting in higher safety factors than in the design condition.